2009
DOI: 10.1089/neu.2009.0955
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Histological Effects of Traumatic Brain Injury in eNOS-Deficient Mice

Abstract: Microvascular dysfunction in the brain, characterized by vasoconstriction, vascular occlusion, and disruption of the blood brain barrier, may adversely affect outcome following traumatic brain injury (TBI). Because of its vasodilating and antiaggregative properties, nitric oxide (NO) produced by nitric oxide synthase in the endothelium (eNOS) is a key regulator of vascular homeostasis. The objective of the present study was to evaluate the role of eNOS in vascular disturbances and histological outcome in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…While additional studies are required to determine the exact contribution of hypertension and insulin resistance to the elevation of Aβ our in vitro data indicate that loss of endothelial NO is sufficient to increase APP, BACE1 and Aβ levels in the absence of any hemodynamic forces or insulin resistance. In addition, existing evidence suggests that hypoperfusion can lead to alterations in brain APP and Aβ levels; however, prior reports demonstrated that cerebral blood flow is normal in eNOS −/− animals17, 18.…”
Section: Discussionmentioning
confidence: 97%
“…While additional studies are required to determine the exact contribution of hypertension and insulin resistance to the elevation of Aβ our in vitro data indicate that loss of endothelial NO is sufficient to increase APP, BACE1 and Aβ levels in the absence of any hemodynamic forces or insulin resistance. In addition, existing evidence suggests that hypoperfusion can lead to alterations in brain APP and Aβ levels; however, prior reports demonstrated that cerebral blood flow is normal in eNOS −/− animals17, 18.…”
Section: Discussionmentioning
confidence: 97%
“…The immunoreactivity of eNOS is increased in the area surrounding the contused area in the first 3 days after experimental trauma (Cobbs et al, 1997). eNOS knockout mice have greater reduction in CBF than wild type variants in the first 2 h after trauma (Lundblad et al, 2009). Genetic variants of eNOS influence the maintenance of CBF after severe TBI.…”
Section: Enos Functionmentioning
confidence: 99%
“…Further, reports from murine models have indicated that inhalation of NO after TBI is neuroprotective and reduces cerebral inflammation, 23,24 whereas other reports have indicated that eNOS-deficient mice have lower cerebral blood flow than wild-type mice after cortical impact. 18 In contrast to this, other reports have linked high brain microdialysate levels of NO to adverse outcome after TBI, 25 whereas results from a murine cortical impact model reported reduced brain edema formation in eNOSdeficient mice. 24 Although these results may seem conflicting, it is likely that TBI-induced dysregulation of the balance between vasoconstrictors, such as ET-1, and vasodilators, such as eNOS and NO, promotes development of the secondary brain injury by inducing local hypoxia through compromised cerebral perfusion.…”
Section: Discussionmentioning
confidence: 93%
“…This is likely primarily owing to superior plasma volume expansion and reduced cerebral edema in the FFP group, contrasted with rapid fluid extravasation into the brain parenchyma in the NS group. Alternatively, the observed favorable brain oxygenation profile in the FFP group may, in part, be associated with an endothelial preservation resulting in better vasomotor control through mediators such as eNOS, 18 with subsequent improvements in cerebral perfusion pressures and brain oxygenation.…”
Section: Discussionmentioning
confidence: 99%